Government Spending on Human Capital Development and Economic Growth in Nigeria: The Interactive Influence of Insecurity - ABBAH, EMMANUEL UMALE; MWANAT, MATTHIAS; BUSARI, TAJUDEEN OLAYIWOLA; UZOMBA, PETER CHIKA (ABUAD Journal of Social and Management Sciences, 2025)
Using the Vector Error Correction Methodology, this research examined the interactive nature of insecurity on the relationship between government spending on human capital development and economic growth in Nigeria from 1992 to 2022. The study revealed that in the long run, recurrent government spending on education and health positively and significantly influenced economic growth. The interactive variable (insecurity and recurrent government spending on education and health) in the long run negatively and significantly affected economic growth in Nigeria. Furthermore, the variance decomposition result revealed that in the short run, recurrent government spending on education and health caused significant variations in economic growth, followed by insecurity and then the interactive variable (insecurity and recurrent government spending on education and health). However, in the long run, the interactive variable (insecurity and recurrent government spending on education and health) has a more significant influence on economic growth, followed by insecurity and lastly, recurrent government spending on education and health. Thus, the study recommended that the government should increase spending on human capital development, especially recurrent government spending on education and health. Furthermore, increased government spending on the country's security apparatus is also advocated.